Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd010414.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the implementation of lay health worker programmes to improve access to maternal and child health: qualitative evidence synthesis

Abstract: Rather than being seen as a lesser trained health worker, LHWs may represent a different and sometimes preferred type of health worker. The close relationship between LHWs and recipients is a programme strength. However, programme planners must consider how to achieve the benefits of closeness while minimizing the potential drawbacks. Other important facilitators may include the development of services that recipients perceive as relevant; regular and visible support from the health system and the community; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
280
1
16

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(311 citation statements)
references
References 103 publications
14
280
1
16
Order By: Relevance
“…Rigorous training and credentialing are important when LHWs are used as HVs. 47 In 1 study, an LHW-nurse HV team compared with a nurse-only approach showed improved uptake and improved access to maternal mental health services but did not improve health outcomes for low-SES infants. 48 -50 Although LHWs as HVs may be a promising, cost-conscious solution based on data in other populations, if families of infants in the NICU do not find these HVs acceptable and helpful, they may not be effective.…”
Section: Homementioning
confidence: 96%
“…Rigorous training and credentialing are important when LHWs are used as HVs. 47 In 1 study, an LHW-nurse HV team compared with a nurse-only approach showed improved uptake and improved access to maternal mental health services but did not improve health outcomes for low-SES infants. 48 -50 Although LHWs as HVs may be a promising, cost-conscious solution based on data in other populations, if families of infants in the NICU do not find these HVs acceptable and helpful, they may not be effective.…”
Section: Homementioning
confidence: 96%
“…The methodological quality of individual studies meeting the inclusion criteria was appraised by two reviewers (AS and AB) using an abbreviated version of the Critical Appraisal Skills Programme (CASP) quality assessment tool for qualitative studies (Critical Appraisal Skills Programme (CASP) 2014) and the CerQual (now Confidence in the Evidence from Reviews of Qualitative research) approach (Glenton et al, 2013). The CerQual approach aims to assess how much certainty could be placed in the qualitative research evidence.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The CerQual approach (Glenton et al, 2013) was used to assess the certainty of the review findings across all intervention types. These were graded as high, moderate, low or very low.…”
Section: Certainty Of the Review Findingmentioning
confidence: 99%
“…Features/factors influencing implementation are examined one by one Using logic models/conceptual framework Factors influencing implementation of lay health worker programmes [44] a School-based behavioural interventions to prevent sexually transmitted infections [59] Contextual features from qualitative research are integrated holistically with findings on effectiveness to develop or refine the logic model Development of framework is flexible and can incorporate stakeholder input when description in published studies is poor Analysing programme theory School feeding programmes for disadvantaged children [54] Interventions to prevent repeat teenage pregnancy [64] a Contextual features from qualitative research are integrated holistically with effectiveness findings to develop and refine programme theory Expertise in programme theory required (e.g.realist evaluation) Testing hypotheses derived using subgroup analysis Promoting positive health behaviours [27] Hypotheses from qualitative synthesis can be tested statistically Requires sufficient numbers of trials to conduct sub-group analysis Features/factors influencing implementation are examined one by one Qualitative comparative analysis.…”
Section: Juxtaposing Findings In a Matrixmentioning
confidence: 99%
“…the balance of benefit and harm of interventions) to underpin clinical guidance. The publication of the first qualitative evidence synthesis in the Cochrane Library signalled growing recognition of both the rigour and utility of this type of review [4][5].…”
Section: Introductionmentioning
confidence: 99%